Factors associated with nutritional status of under five children among Satar Community of Bhadrapur Municipality, Jhapa, Nepal - Sangroula, Raj Kumar; Uprety, Srijana (International Journal Of Community Medicine And Public Health, 2020)
Background: Adequate feeding is basic right of human being. According to NDHS 2016, prevalence of stunting, wasting and underweight are 36%, 10% and 27% respectively. The prevalence may be more in underprivileged community like Satar community who reside in eastern part of Nepal. This study was conducted to assess the factors associated with under nutrition of under five years children of Satar community in Bhadrapur Municipality. Methods: A community based cross sectional study was conducted in Bhadrapur Municipality of Jhapa district which were purposively selected. Four wards where Satar community reside were selected for collection of data. Verbal informed consent was taken from the mothers of the under five children and approval was taken from research committee of Central Institute of Science and Technology College. Bivariate analysis was performed to detect the factors associated with nutrition status of children. Results: In the study, prevalence of stunting, wasting and underweight were high as compared to national data i.e. 39.5%, 14.2% and 29.5% percent respectively. The study found that maternal education, paternal education, family income, exclusive breastfeeding and food frequency was significantly associated with under nutrition (stunting, wasting and underweight). Stunting was significantly associated with age of child and mother and religion. Underweight was associated with religion and weaning of children. Conclusions: High prevalence of stunting, wasting and underweight are due to socio demographic factors like religion, educational status of father and mother, family income and child feeding practice. Programs should be focused on socio demographic and economic factors and child feeding practice to reduce problem of malnutrition.